Unusual Middle Kingdom Funerary Stela of a Man at Alexandria National Museum no. 223 - Aman, Marzouk Al-Sayed.
Publication of a Middle Kingdom stela, is exhibited in Alexandria National Museum (Inv. No. 223), including comments on the style, iconography, paleography, and dating criteria.   doi: http://dx.doi.org/10.5913/jarce.53.2017.a008